Organizational aspects of ICT applications in cultural heritage “Virtual Museum” context: the permanent challenge of reconciliation of diverging scientific, technical, operational and financial objectives. - Georgios Giannoulis-Giannoulopoulos (Virtual Archaeology Review)
The applications of ICT in the cultural heritage field are including a new expanding category of applications, having a “creative” character, and a multidisciplinary approach. Motivations and priorities of involved players (individuals and organizational players), are presented, through various FHW paradigm projects, in order to explore the possible impact of this kind of projects in science and cultural heritage concept, as well as to explore their hidden added value, that makes them capable to attract resources.